Ancestry informative markers and complete blood count parameters in Brazilian blood donors - Felix, Gabriela E. S. (2010)
A complete blood count is very useful in clinical diagnoses when reference ranges are well established for the population. Complete blood counts and allele frequencies of Ancestry Informative Markers (AIMs) were analyzed in Brazilians with the aim of characterizing the hematological values of an admixed population. Positive associations were observed between gender and neutrophils, monocytes, eosinophils, erythrocytes, hemoglobin, hematocrit, MCV, MCHC and platelet counts. No significant differences were found for age, alcohol consumption, educational status, ethnicity, smoking in respect to the complete blood count values. In general, men had higher red blood cell values, while women had higher values for white blood cells and platelets. The study of the population was highly heterogeneous with mean proportions (± SE) of African, European and Amerindian ancestry being 49.0 ± 3.0%, 44.0 ± 9.0% and 7.0 ± 9.0%, respectively. Amerindian ancestry showed limited contribution to the makeup of the population, but estimated ancestral proportions were statistically significant (r = 0.9838; P<0.001). These hematologic values are similar to Afro-Americans, another admixed population.